VmPacC Is Required for Acidification and Virulence in Valsa mali - Wu, Yuxing; Yin, Zhiyuan; Xu, Liangsheng; Feng, Hao; Huang, Lili (Frontiers in Microbiology, 2018)
The role of the transcription factor PacC has been characterised in several pathogenic fungi, and it affects virulence via several mechanisms. In this study, we examined the role of the PacC homolog VmPacC in Valsa mali, the causal agent of apple canker disease. We found that the expression of VmPacC was up-regulated in neutral and alkaline pH and during infection. At pH 6–10, the radial growth of a VmPacC deletion mutant decreased compared to wild-type. In addition, the sensitivity to oxidative stress of the VmPacC deletion mutant was impaired, as its growth was more severely inhibited by H2O2 than that of the wild-type. The lesion size caused by the VmPacC deletion mutant was smaller than that of the wild-type on apple leaves and twigs. Interestingly, expression of pectinase genes increased in deletion mutant during infection. To further confirm the negative regulation, we generated dominant activated C-27 allele mutants that constitutively express VmPacC. The pectinase activity of activated mutants was reduced at pH 4. We further observed that V. mali can acidify the pH during infection, and that the capacity for acidification was impaired after VmPacC deletion. Furthermore, VmPacC is involved in the generation of citric acid, which affects virulence. These results indicate that VmPacC is part of the fungal responses to neutral and alkaline pH and oxidative stress. More importantly, VmPacC is required for acidification of its environment and for full virulence in V. mali.